Socket.io Real-time Web Application Development. - Rai, Rohit (Packt Pub., 2013)
Socket.io Real-time Web Application Development.
Keywords: Web applications -- Development.; Application software -- Development.; JavaScript (Computer program language); elektronické knihy; electronic books